1996
DOI: 10.1111/j.1600-0773.1996.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effect of Aluminium Ingestion on Bone in Calcium‐Deficient Rats

Abstract: In order to elucidate the relationship of osteogenesis with aluminum and iron deposition, we investigated the histopathological findings of bone in calcium and/or aluminium-deficient rats, together with levels of calcium, aluminium and iron in sera and bone tissues, and also the level of serum parathyroid hormone. Four week old male STD-Wistar rats were divided into four groups to examine the effects of four kinds of diets for ten weeks. The rats on normal diet (Group I) and normal diet+aluminum (Group II) did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Decreased Al urinary excretion caused by impaired renal function with, possibly, an increase in gastrointestinal absorption of Al results in increased Al load leading to markedly increased bone Al levels and the presence of Al between the junction of calcified and non-calcified bones (Alfrey, 1993). Longterm oral exposure to Al results in an increase in Al levels in the bone (Ahn et al, 1995;Konishi et al, 1996) that is responsible for the bone disease.…”
Section: Musculoskeletal Effectsmentioning
confidence: 99%
“…Decreased Al urinary excretion caused by impaired renal function with, possibly, an increase in gastrointestinal absorption of Al results in increased Al load leading to markedly increased bone Al levels and the presence of Al between the junction of calcified and non-calcified bones (Alfrey, 1993). Longterm oral exposure to Al results in an increase in Al levels in the bone (Ahn et al, 1995;Konishi et al, 1996) that is responsible for the bone disease.…”
Section: Musculoskeletal Effectsmentioning
confidence: 99%
“…After administration to mice of 900 mg Al, Golub et al (1995) found lower Fe levels in the brain and cerebrospinal fluid. Konishi et al (1996), in addition to aluminium also detected Fe in the frontal region of bone mineralization.…”
Section: Discussionmentioning
confidence: 77%
“…Calcium-deficient diet causes increase in Al contents in serum and bones of rats, not given this element, probably due to bones of such animals being more fragile (Konishi et al 1996). Brown & Schwartz (1992) assumed that aluminium binds with ligands at the same sites as Fe 3π , and they observed significant Al increase in the liver and spleen of rats fed iron-deficient diet.…”
Section: Discussionmentioning
confidence: 99%
“…Fe deposition at the mineralization front of bones was reported in the aluminum‐induced osteomalacia of dialysis patients and in an animal model (Forero, Altamirano, & Ramos, 1998; Konishi et al, 1996; Matsushima, Torii, Ozaki, & Narama, 2003; Miyoshi, Saito, Bandobashi, Ohtsuki, & Taguchi, 2006; Pierides & Myli, 1984). Additionally, diseases characterized by iron overload such as thalassemia, hereditary hemochromatosis, and treatment of anemia caused bone loss in association with Fe deposition at the mineralization front (Mahachoklertwattana et al, 2003; Noda, Yasuda, & Kitagawa, 1991; Sato & Shiraki, 1998).…”
Section: Discussionmentioning
confidence: 94%